(untitled) (INNOVATIVE ECONOMY, 2022)
Zhyvko M.A., Honak I.M., Ivashchuk O.V., Prints V.A. ECONOMIC RIVALRY OF COUNTRIES IN THE CONTEXT OF THE MILITARIZATION OF NATIONAL ECONOMIES Purpose. The aim of the article is to disclose the peculiarities of the implementation of economic rivalry by countries with the growing militarization of national economies and assessment of the dependence of competitiveness of countries on strategic imperatives of economic rivalry, among which are some indicators of militarization. Methodology of research. General scientific and special methods were used to achieve this goal: historical-logical and theoretical generalization - to form the conceptual apparatus of research; abstract and logical - for formulating hypotheses and conclusions; analysis, synthesis, quantitative comparison and generalization - in order to identify the positions of countries on the indicators selected for the study; econometric modelling and visualization - in order to graphically display the results of the study. Findings. The characteristic permanence of challenges, threats and gaps in the economic rivalry of countries in the conditions of strengthening the processes of militarization of the global economy is studied. The positioning of countries according to the Global Competitiveness Index and GDP per capita, the Military Strength Index and the Global Competitiveness Index in 2019 has been carried out. The world military expenditures in 2010-2018 are analysed, as well as the change in military expenditures by sub-regions of the world and the share of exporting countries in the world arms market in 2014-2018, which allowed to identify global economic imperatives that significantly affect economic rivalry countries and strengthening competitive positions. Originality. A theoretical model of economic rivalry in the global economy was developed, which allowed us to find out that the militarization of economies reflects the shift of emphasis in the global economy to forceful methods of influencing economic processes, in contrast to other studied imperatives. Practical value. The main provisions of this study in the form of evaluation proposals can be used to identify strategic imperatives of economic rivalry between countries in the militarization of national economies. Key words: global economy, economic rivalry, competitive advantages, competitiveness, international trade, militarization of economies.